Anti-CCP Antibodies in Unaffected First-Degree Relatives of Rheumatoid Arthritis Patient (Medicine Today, 2024)
Introduction: Rheumatoid arthritis (RA) is perhaps the most common inflammatory arthritis, affecting 0.5% to 1% of the general population worldwide. Environmental and genetic influences are important risk factors for pathogenesis of RA. First-degree relatives (FDRs) of RA patients sharing genetic and environmental risk factors for RA may represent as pre-RA state. Since anti-CCP antibody appears years before the onset of RA, it can be used to estimate risk-potential for future development of RA in unaffected FDRs of RA patient. Objective: To see the serum anti-CCP antibody in unaffected FDRs of RA patients. Materials and Methods: This cross-sectional study was conducted from July 2019 to June 2020 in Department of Biochemistry, Dhaka Medical College, Dhaka. A total number of 50 subjects were selected among which 25 were unaffected FDRs of RA patients and the other 25 were age & gender matched healthy subjects. The related RA patients were selected from Rheumatology outdoor, Department of Rheumatology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka and the healthy subjects were taken from the attendants came to the same institute who did not have RA patient in their family. The key variables (age and gender) were recorded and outcome variable (anti-CCP antibody in study subjects) was estimated. Statistical analysis was done by SPSS 26.0 and the significance was defined as p < 0.05. Results: Mean age of the FDRs of RA patient was 31.36 ± 10.51 years and that of healthy subjects was 31.56 ± 8.89 years. Most of the participants were in age group 20-29 years followed by 30-39 years. 4% of FDRs of RA patient were anti-CCP antibody positive and no positive case was recorded in healthy subjects. The median level of anti-CCP antibody in FDRs of RA patient was 0.50 U/mL and that in healthy subjects was 0.09 U/mL. The level of significance (p = 0.002) showed that serum anti-CCP antibody level was significantly higher (within normal range) in FDRs of RA patient than in healthy subjects, which was even more significant in FDRs of seropositive RA patients. Conclusion: This study revealed that serum anti-CCP antibody level was significantly higher (within normal range) in FDRs of RA patient than in healthy subjects and the proportion of positive anti-CCP antibody was more in FDRs of RA patient than in healthy subjects.Medicine Today 2024, Vol.36 (2): 76-81